Un référentiel nouveau de gestion de la chose publique éducative française - Michel Warren (Recherches en Éducation)
The meaning of the French school management reference is explained on the basis of public education rationales and policies. School was and remains a political and national issue. Before the cultural, ideological and institutional changeover of the 1980s, school territorialization was overshadowed by an universalist and national ideology, and by lay and normative basis, both acquired during the Third Republic. Why does the state decide, from the 1980s, to make various changes in the management of public education policies? In a context of political, management and geo-administrative territorialization, how do the relations between the state, school and local evolve? What are the rationales and processes that contribute to influencing the political and economic perception of the European Union (EU) in the education field? Territorialization produces new ways of linking national and local, which are part of a double political will of the state to redistribute power, and to fight against social inequalities at school. It expresses a new cultural, ideological and political reference for the Republic school management. French public education policies refer to the strategic design of the Lisbon European Council (2000): « Becoming the most competitive and the most dynamic knowledge economy in the world. » The Lisbon Process reflects the EU political perception of education, based on the will to involve the subject « knowledge » into an economic and social dynamics. Will the new management reference of public education policies, defended by the republican ideal and the EU, be able to promote a principle of socio-human solidarity on a territory spread from local to global?